FAS2FURIOUS: Moderate-Throughput Secreted Expression of Difficult Recombinant Proteins in Drosophila S2 Cells - Coker, Jesse A.; Katis, Vittorio L.; Fairhead, Michael; Schwenzer, Anja; Clemmensen, Stine B.; Frandsen, Bent U.; de Jongh, Willem A.; Gileadi, Opher; Burgess-Brown, Nicola A.; Marsden, Brian D.; Midwood, Kim S.; Yue, Wyatt W. (Frontiers in Bioengineering and Biotechnology, 2022)
Recombinant protein expression in eukaryotic insect cells is a powerful approach for producing challenging targets. However, due to incompatibility with standard baculoviral platforms and the existing low-throughput methodology, use of the Drosophila melanogaster “S2” cell line lags behind more common insect-cell lines like Sf9 or High-Five™. Due to the advantages of S2 cells, particularly for secreted and secretable proteins, the lack of a simple and parallelizable S2-based platform represents a bottleneck, particularly for biochemical and biophysical laboratories. Therefore, we developed FAS2FURIOUS, a holistic and rapid S2 expression pipeline built upon an existing low-throughput commercial platform. FAS2FURIOUS is comparable in effort to simple E. coli systems and allows us to clone and test up to forty-six constructs in just two weeks. Given the ability of S2 cells to express challenging targets, including receptor ectodomains, secreted glycoproteins, and viral antigens, FAS2FURIOUS represents an attractive orthogonal approach for protein expression in eukaryotic cells.